Future U.S. Workforce for Geospatial Intelligence - National Research Council (The National Academies Press, 2013)
We live in a changing world with multiple and evolving threats to national security, including terrorism, asymmetrical warfare (conflicts between agents with different military powers or tactics), and social unrest. Visually depicting and assessing these threats using imagery and other geographically-referenced information is the mission of the National Geospatial-Intelligence Agency (NGA). As the nature of the threat evolves, so do the tools, knowledge, and skills needed to respond. The challenge for NGA is to maintain a workforce that can deal with evolving threats to national security, ongoing scientific and technological advances, and changing skills and expectations of workers. Future U.S. Workforce for Geospatial Intelligence assesses the supply of expertise in 10 geospatial intelligence (GEOINT) fields, including 5 traditional areas (geodesy and geophysics, photogrammetry, remote sensing, cartographic science, and geographic information systems and geospatial analysis) and 5 emerging areas that could improve geospatial intelligence (GEOINT fusion, crowdsourcing, human geography, visual analytics, and forecasting). The report also identifies gaps in expertise relative to NGA's needs and suggests ways to ensure an adequate supply of geospatial intelligence expertise over the next 20 years.
Keywords: Conflict and Security Issues; Earth Sciences

Geotargeted Alerts and Warnings: Report of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2013)
Geotargeted Alerts and Warnings: Report of a Workshop on Current Knowledge and Research Gaps is the summary of a February, 2013 workshop convened by the Computer Science and Telecommunications Board of the National Research Council to examine precise geotargeting of public alerts and warnings using social media. The workshop brought together social science researchers, technologists, emergency management professionals, and other experts to explore what is known about how the public responds to geotargeted alerts and warnings, technologies and techniques for enhancing the geotargeting of alerts and warnings, and open research questions about how to effectively use geotargeted alerts and warnings and technology gaps. This report considers the potential for more precise geographical targeting to improve the effectiveness of disaster alerts and warnings; examines the opportunities presented by current and emerging technologies to create, deliver, and display alerts and warnings with greater geographical precision; considers the circumstances where more granular targeting would be useful; and examines the potential roles of federal, state, and local agencies and private sector information and communications providers in delivering more targeted alerts.
Keywords: Conflict and Security Issues; Computers and Information Technology

Effects of U.S. Tax Policy on Greenhouse Gas Emissions - National Research Council (The National Academies Press, 2013)
The U.S. Congress charged the National Academies with conducting a review of the Internal Revenue Code to identify the types of and specific tax provisions that have the largest effects on carbon and other greenhouse gas emissions and to estimate the magnitude of those effects. To address such a broad charge, the National Academies appointed a committee composed of experts in tax policy, energy and environmental modeling, economics, environmental law, climate science, and related areas. For scientific background to produce Effects of U.S. Tax Policy on Greenhouse Gas Emissions, the committee relied on the earlier findings and studies by the National Academies, the U.S. government, and other research organizations. The committee has relied on earlier reports and studies to set the boundaries of the economic, environmental, and regulatory assumptions for the present study. The major economic and environmental assumptions are those developed by the U.S. Energy Information Administration (EIA) in its annual reports and modeling. Additionally, the committee has relied upon publicly available data provided by the U.S. Environmental Protection Agency, which inventories greenhouse gas (GHG) emissions from different sources in the United States. The tax system affects emissions primarily through changes in the prices of inputs and outputs or goods and services. Most of the tax provisions considered in this report relate directly to the production or consumption of different energy sources. However, there is a substantial set of tax expenditures called "broad-based" that favor certain categories of consumption—among them, employer-provided health care, owner-occupied housing, and purchase of new plants and equipment. Effects of U.S. Tax Policy on Greenhouse Gas Emissions examines both tax expenditures and excise taxes that could have a significant impact on GHG emissions.
Keywords: Industry and Labor; Environment and Environmental Studies

Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2013)
Following an earlier NRC workshop on public response to alerts and warnings delivered to mobile devices, a related workshop was held on February 28 and 29, 2012 to look at the role of social media in disaster response. This was one of the first workshops convened to look systematically at the use of social media for alerts and warnings—an event that brought together social science researchers, technologists, emergency management professionals, and other experts on how the public and emergency managers use social media in disasters.In addition to exploring how officials monitor social media, as well as the resulting privacy considerations, the workshop focused on such topics as: what is known about how the public responds to alerts and warnings; the implications of what is known about such public responses for the use of social media to provide alerts and warnings to the public; and approaches to enhancing the situational awareness of emergency managers. Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps summarizes presentations made by invited speakers, other remarks by workshop participants, and discussions during parallel breakout sessions. It also points to potential topics for future research, as well as possible areas for future research investment, and it describes some of the challenges facing disaster managers who are seeking to incorporate social media into regular practice.
Keywords: Conflict and Security Issues; Computers and Information Technology

Frontiers in Massive Data Analysis - National Research Council (The National Academies Press, 2013)
Data mining of massive data sets is transforming the way we think about crisis response, marketing, entertainment, cybersecurity and national intelligence. Collections of documents, images, videos, and networks are being thought of not merely as bit strings to be stored, indexed, and retrieved, but as potential sources of discovery and knowledge, requiring sophisticated analysis techniques that go far beyond classical indexing and keyword counting, aiming to find relational and semantic interpretations of the phenomena underlying the data. Frontiers in Massive Data Analysis examines the frontier of analyzing massive amounts of data, whether in a static database or streaming through a system. Data at that scale--terabytes and petabytes--is increasingly common in science (e.g., particle physics, remote sensing, genomics), Internet commerce, business analytics, national security, communications, and elsewhere. The tools that work to infer knowledge from data at smaller scales do not necessarily work, or work well, at such massive scale. New tools, skills, and approaches are necessary, and this report identifies many of them, plus promising research directions to explore. Frontiers in Massive Data Analysis discusses pitfalls in trying to infer knowledge from massive data, and it characterizes seven major classes of computation that are common in the analysis of massive data. Overall, this report illustrates the cross-disciplinary knowledge--from computer science, statistics, machine learning, and application disciplines--that must be brought to bear to make useful inferences from massive data.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Guidebook on Integrating GIS in Emergency Management at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Report 88: Guidebook on Integrating GIS in Emergency Management at Airports is designed to help airports identify needs and assess current capabilities with respect to using geographical information systems (GIS) in emergency management (EM).The report discusses GIS and emergency management and provides a roadmap for airports to move from their current state of GIS implementation (even if they do not yet have any form of GIS) to the point of integrating into emergency management and coordinating with mutual aid partners.The guidebook contains a CD-ROM with case studies and key lessons learned from airports that have integrated GIS into EM. The guidance concludes with a checklist of how to maintain and keep EM plans relevant and current.The project that developed ACRP Report 88 also produced a PowerPoint presentation that outlines the benefits of integrating GIS into EM, which is also available on the CD-ROM.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Zero-Sustainment Aircraft for the U.S. Air Force: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Overall Air Force weapon system sustainment (WSS) costs are growing at more than 4 percent per year, while budgets have remained essentially flat. The cost growth is due partly to aging of the aircraft fleet, and partly to the cost of supporting higher-performance aircraft and new capabilities provided by more complex and sophisticated systems, such as the latest intelligence, surveillance, and reconnaissance (ISR) platforms. Furthermore, the expectation for the foreseeable future is that sustainment budgets are likely to decrease, so that the gap between budgets and sustainment needs will likely continue to grow wider. Most observers accept that the Air Force will have to adopt new approaches to WSS if it is going to address this problem and remain capable of carrying out its missions. In this context, the original intent of this 3-day workshop was to focus on ways that science and technology (S&T) could help the Air Force reduce sustainment costs. However, as the workshop evolved, the discussions focused more and more on Air Force leadership, management authority, and culture as the more critical factors that need to change in order to solve sustainment problems. Many participants felt that while S&T investments could certainly help—particularly if applied in the early stages ("to the left") of the product life cycle—adopting a transformational management approach that defines the user-driven goals of the enterprise, empowers people to achieve them, and holds them accountable, down to the shop level. Several workshop participants urged Air Force leaders to start the process now, even though it will take years to percolate down through the entire organization. These sustainment concerns are not new and have been studied extensively, including recent reports from the National Research Council's Air Force Studies Board and the Air Force Scientific Advisory Board.
Keywords: Conflict and Security Issues; Space and Aeronautics

Model Mutual Aid Agreements for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 45: Model Mutual Aid Agreements for Airports presents information on mutual aid agreements, addressing nearly every type of emergency that could affect airports and require outside resources. The report is designed to assist airport operators in creating and sustaining effective emergency management mutual aid partnerships by documenting the specifics of existing agreements.
Keywords: Transportation and Infrastructure

Environmental Assessment of Air and High-Speed Rail Corridors - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 43: Environmental Assessment of Air and High-Speed Rail Corridors explores where additional research can improve the ability to assess the environmental outcomes of these two systems.
Keywords: Transportation and Infrastructure

Energy Reduction at U.S. Air Force Facilities Using Industrial Processes: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The Department of Defense (DoD) is the largest consumer of energy in the federal government. In turn, the U.S. Air Force is the largest consumer of energy in the DoD, with a total annual energy expenditure of around $10 billion. Approximately 84 percent of Air Force energy use involves liquid fuel consumed in aviation whereas approximately 12 percent is energy (primarily electricity) used in facilities on the ground. This workshop was concerned primarily with opportunities to reduce energy consumption within Air Force facilities that employ energy intensive industrial processes—for example, assembly/disassembly, painting, metal working, and operation of radar facilities—such as those that occur in the maintenance depots and testing facilities. Air Force efforts to reduce energy consumption are driven largely by external goals and mandates derived from Congressional legislation and executive orders. To date, these goals and mandates have targeted the energy used at the building or facility level rather than in specific industrial processes. In response to a request from the Deputy Assistant Secretary of the Air Force for Energy and the Deputy Assistant Secretary of the Air Force for Science, Technology, and Engineering, the National Research Council, under the auspices of the Air Force Studies Board, formed the Committee on Energy Reduction at U.S. Air Force Facilities Using Industrial Processes: A Workshop. The terms of reference called for a committee to plan and convene one 3 day public workshop to discuss: (1) what are the current industrial processes that are least efficient and most cost ineffective? (2) what are best practices in comparable facilities for comparable processes to achieve energy efficiency? (3) what are the potential applications for the best practices to be found in comparable facilities for comparable processes to achieve energy efficiency? (4) what are constraints and considerations that might limit applicability to Air Force facilities and processes over the next ten year implementation time frame? (5) what are the costs and paybacks from implementation of the best practices? (6) what will be a proposed resulting scheme of priorities for study and implementation of the identified best practices? (7) what does a holistic representation of energy and water consumption look like within operations and maintenance?
Keywords: Energy and Energy Conservation; Conflict and Security Issues

Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The U. S. Air force currently invests significantly in science and technology for directed-energy weapon (DEW) systems. Key elements of this investment include high-energy lasers and high-power microwaves. Other DEW research and development efforts include: optical beam control for high-energy lasers; vulnerability and lethality assessments; and advanced non-conventional and innovative weapons. Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications is the summary of three workshop sessions convened between February and April, 2013 by the Air Force Studies Board of the National Academies' National Research Council. Representatives from the Air Force science and technology community and DEW experts from the U.S. Army, U.S. Navy, Office of the Secretary of Defense, and the Defense Advanced Research Projects Agency presented and discussed threats that DEW capabilities might defend against and assessments of foreign progress in DEW. This report examines the current status of DEW capabilities both in the U.S. and abroad, and considers future applications of DEW systems.
Keywords: Conflict and Security Issues

Leveraging Action to Support Dissemination of the Pregnancy Weight Gain Guidelines: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Since 1990, when the last guidelines for weight gain during pregnancy were issued, the average body weight of women entering their childbearing years has increased considerably, with a greater percentage of these women now classified as overweight or obese. Women of childbearing age are also more likely to have chronic conditions such as high blood pressure or diabetes and to be at risk for poor maternal and child health outcomes. All of these factors increase the likelihood of poor pregnancy outcomes for women and their infants. As part of the continuing effort of The Institute of Medicine (IOM) and the National Research Council (NRC) to promote the revised pregnancy weight gain guidelines recommended in their 2009 study Weight Gain During Pregnancy: Reexamining the Guidelines, the IOM and NRC convened a workshop in March, 2013, to engage interested stakeholders, organizations, and federal agencies in a discussion of issues related to encouraging behavior change that would reflect the updated guidelines on weight gain during pregnancy. During the workshop, the IOM and NRC presented newly developed information resources to support guidance based on the recommendations of the 2009 report. Leveraging Action to Support Dissemination of the Pregnancy Weight Gain Guidelines summarizes the workshop's keynote address and the various presentations and discussions from the workshop, highlighting issues raised by presenters and attendees. Interested stakeholders, organizations, health professionals, and federal agencies met to discuss issues related to encouraging behavior change that would reflect the updated guidelines on weight gain during pregnancy. This report discusses conceptual products as well as products developed for dissemination, ways to facilitate and support behavior change to achieve healthy weight pre- and postpregnancy, and how to put the weight gain guidelines into action to implement change.
Keywords: Health and Medicine; Food and Nutrition

U.S. Air Force Strategic Deterrence Capabilities in the 21st Century Security Environment: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Changes in the 21st century security environment require new analytic approaches to support strategic deterrence. Because current adversaries may be deterred from the use of nuclear weapons differently than were Cold War adversaries, the Air Force needs an analytic process and tools that can help determine those Air Force capabilities that will successfully deter or defeat these new nuclear-armed adversaries and assure U.S. allies. While some analytic tools are available, a coherent approach for their use in developing strategy and policy appears to be lacking. Without a coherent analytic approach that addresses the nuances of today's security environment, Air Force views of its strategic deterrence needs may not be understood or accepted by the appropriate decision makers. A coherent approach will support Air Force decisions about its strategic force priorities and needs, deter actual or potential adversaries, and assure U.S. allies. In this context, the Air Force in 2012 requested that the Air Force Studies Board of the National Research Council undertake a workshop to bring together national experts to discuss current challenges relating strategic deterrence and potential new tools and methods that the Air Force might leverage in its strategic deterrence mission. The workshop consisted of two 3-day sessions held in Washington, DC on September 26-28, 2012 and January 29-31, 2013 and was attended by a very diverse set of participants with expertise in strategic deterrence and a range of analytic tools of potential interest to the Air Force. U.S. Air Force Strategic Deterrence Capabilities in the 21st Century Security Environment summarizes this workshop.
Keywords: Conflict and Security Issues

Best Available and Safest Technologies for Offshore Oil and Gas Operations: Options for Implementation - National Academy of Engineering; National Research Council (The National Academies Press, 2013)
Best Available and Safest Technologies for Offshore Oil and Gas Operations: Options for Implementation explores a range of options for improving the implementation of the U.S. Department of the Interior's congressional mandate to require the use of best available and safety technologies in offshore oil and gas operations. In the Outer Continental Shelf Lands Act, Congress directs the Secretary of the Interior to regulate oil and gas operations in federal waters. The act mandates that the Secretary "shall require, on all new drilling and production operations and, wherever practicable, on existing operations, the use of the best available and safest technologies which the Secretary determines to be economically feasible, wherever failure of equipment would have a significant effect on safety, health, or the environment, except where the Secretary determines that the incremental benefits are clearly insufficient to justify the incremental costs of utilizing such technologies." This report, which was requested by Department of the Interior's Bureau of Safety and Environmental Enforcement (BSEE), also reviews options and issues that BSEE is already considering to improve implementation of the best available and safest technologies requirement.
Keywords: Engineering and Technology; Energy and Energy Conservation

Sag Vertical Curve Design Criteria for Headlight Sight Distance - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 198: Sag Vertical Curve Design Criteria for Headlight Sight Distance reviews the current methodologies used in the design of sag vertical curves and changes in headlamp technologies. The report also highlights potential changes to the American Association of State Highway and Transportation Officials (AASHTO) design guide as a result of these reviews.
Keywords: Transportation and Infrastructure

Delivering Affordable Cancer Care in the 21st Century: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Rising health care costs are a central fiscal challenge confronting the United States. National spending on health care currently accounts for 18 percent of gross domestic product (GDP), but is anticipated to increase to 25 percent of GDP by 2037. The Bipartisan Policy Center argues that "this rapid growth in health expenditures creates an unsustainable burden on America's economy, with far-reaching consequences". These consequences include crowding out many national priorities, including investments in education, infrastructure, and research; stagnation of employee wages; and decreased international competitiveness.In spite of health care costs that far exceed those of other countries, health outcomes in the United States are not considerably better. With the goal of ensuring that patients have access to high-quality, affordable cancer care, the Institute of Medicine's (IOM's) National Cancer Policy Forum convened a public workshop, Delivering Affordable Cancer Care in the 21st Century, October 8-9, 2012, in Washington, DC. Delivering Affordable Cancer Care in the 21st Century summarizes the workshop.
Keywords: Health and Medicine

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.
Keywords: Health and Medicine

A Framework for Improving Travel Time Reliability - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-L17-RW-1: A Framework for Improving Travel Time Reliability describes the results of a project designed to identify and enhance the dissemination of transportation systems management and operations (TSM&O) information.A major component of Reliability Project L17 was development of a Knowledge Transfer System (KTS), a web-based tool designed to provide convenient one-stop access to the complete range of TSM&O information. The KTS tool is currently available.Reliability Project L17 also produced the following six items to fill in gaps in knowledge about transportation systems management and operations:Gap-Filling Project 1: CEO Briefing Book on Effective Operations Improvement StrategiesGap-Filling Project 2: Deployment Guidance for TSM&O StrategiesGap-Filling Project 3: Best Practices for TSM&O Program and Budget DevelopmentGap-Filling Project 4: A Guidebook for Standard Reporting and Evaluation Procedures for TSM&O StrategiesGap-Filling Project 5: Guidebook: Placing a Value on Time ReliabilityGap-Filling Project 6: Business Case Primer Communicating the Value of Transportation Systems Management and Operations
Keywords: Transportation and Infrastructure

Sharing Clinical Research Data: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Pharmaceutical companies, academic researchers, and government agencies such as the Food and Drug Administration and the National Institutes of Health all possess large quantities of clinical research data. If these data were shared more widely within and across sectors, the resulting research advances derived from data pooling and analysis could improve public health, enhance patient safety, and spur drug development. Data sharing can also increase public trust in clinical trials and conclusions derived from them by lending transparency to the clinical research process. Much of this information, however, is never shared. Retention of clinical research data by investigators and within organizations may represent lost opportunities in biomedical research. Despite the potential benefits that could be accrued from pooling and analysis of shared data, barriers to data sharing faced by researchers in industry include concerns about data mining, erroneous secondary analyses of data, and unwarranted litigation, as well as a desire to protect confidential commercial information. Academic partners face significant cultural barriers to sharing data and participating in longer term collaborative efforts that stem from a desire to protect intellectual autonomy and a career advancement system built on priority of publication and citation requirements. Some barriers, like the need to protect patient privacy, pre- sent challenges for both sectors. Looking ahead, there are also a number of technical challenges to be faced in analyzing potentially large and heterogeneous datasets. This public workshop focused on strategies to facilitate sharing of clinical research data in order to advance scientific knowledge and public health. While the workshop focused on sharing of data from preplanned interventional studies of human subjects, models and projects involving sharing of other clinical data types were considered to the extent that they provided lessons learned and best practices. The workshop objectives were to examine the benefits of sharing of clinical research data from all sectors and among these sectors, including, for example: benefits to the research and development enterprise and benefits to the analysis of safety and efficacy. Sharing Clinical Research Data: Workshop Summary identifies barriers and challenges to sharing clinical research data, explores strategies to address these barriers and challenges, including identifying priority actions and "low-hanging fruit" opportunities, and discusses strategies for using these potentially large datasets to facilitate scientific and public health advances.
Keywords: Health and Medicine; Policy for Science and Technology

Review of NOAA Working Group Report on Maintaining the Continuation of Long-term Satellite Total Solar Irradiance Observation - National Research Council (The National Academies Press, 2013)
Solar irradiance is a vital source of energy input for the Earth's climate system and its variability has the potential to mitigate or exacerbate a human-created climate. Maintaining an unbroken record of Total Solar Irradiance (TSI) is critical in resolving ongoing debates regarding the potential role of solar variability in influencing Earth's climate. Space-borne instruments have acquired TSI data since 1978. Currently, the best calibrated and lowest noise source of TSI measurements is the Total Irradiance Monitor (TIM) onboard NASA's Solar Radiation and Climate Experiment (SORCE). These TIM-era data are of higher quality than the older data in the full record. Thus, the TSI climate data record (CDR) has two components. There is the shorter, but more accurate record of the TIM era and the full (33+ year) space-based TSI measurement record. Both are important and require preservation. Review of NOAA Working Group Report on Maintaining the Continuation of Long-Term Satellite Total Irradiance Observations evaluates NOAA's plan for mitigating the loss of total solar irradiance measurements from space, given the likelihood of losing this capacity from instruments currently on the SORCE satellite in coming years and the short term/experimental nature of the currently identified method of filling the data gap. This report evaluates NOAA's plan for mitigating the gap in total solar irradiance data.
Keywords: Space and Aeronautics; Earth Sciences